PEMBANGUNAN PENDIDIKAN DAN MDGs DI INDONESIA Sebuah Refleksi Kritis - Dyah Ratih Sulistyastuti (Jurnal Kependudukan Indonesia, 2007)
The second goal of MDGs is to provide basic education for all. This goal is targeted to guarantee that in 2015 all children both boys and girls finish primary schooling. The achievement of this goal is evaluated based on four indicators, namely: schooll enrollment ratio, literacy rate, length of study and ratio between boy and girls students. Indonesian achievement in materialising the second MDGs based on schooll enrollment ratio is good, that is more than 90 percent. The same story is also happen with the literacy rate. However, if it is measured from length of study, Indonesia is still lack behind. This paper is aimed to discuss this issue. The first part of this paper discusses the importance ofMDGs programmes which are fonnulated using right based approach for education. The second part describing various Indonesia's programmes aimed to realise the second MDGs to provide basic education for all. The third part is a review on the achievement of indonesia's eduication programmes in realiasing the second MDGs. The last part is conclusion.Key words: Education, Millenium development goals, MDGs